Dynamics of Price Growth of Curly Red Chili and Red Chili in Kolaka District - Lukman Hakim; Kartomo Kartomo; Nursalam Nursalam (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2020)
This study aims to: 1) Identify the price data pattern of Curly Red Chili and red chilies in Kolaka Regency; 2) Obtain the best time series forecasting method for forecasting the price of Curly Red Chili and ordinary red chilies in Kolaka Regency; 3) Get a forecast for the price of Curly Red Chili and regular red chilies for the coming year. This type of research is descriptive quantitative, the source of the data in this study is secondary data obtained from the office of industry and trade, Kolaka district. The data analysis method used is the time series forecasting method.The results showed that: 1) The results of the identification of data patterns on the plot of price data for Curly Red Chili and common red chilies in Kolaka Regency in 2015-2019 obtained a seasonal pattern. 2) The results of the application of the time series forecasting method for the price of curly red chilies, obtained the best time series forecasting method, namely the box-jenkins method of the SARIMA (1,0,0) (2,0,0) 12 model with the smallest MSE value, namely MSE = 41,534 590 While for the price of ordinary red chilies, the best time series forecasting method is the box-jenkins method of the SARIMA (1,0,0) (1,0,0) 12 model with the smallest MSE value, namely MSE = 44,764,512. 3) The results of forecasting the price of Curly Red Chili using the box-jenkins method SARIMA (1,0,0) (2,0,0) 12 with the help of the MINITAB 19 program is the highest price of IDR 47,355.4 / Kg which occurred in August 2020 and the lowest price is IDR 23,169 / Kg which occurred in January 2020, while the average price of Curly Red Chili in 2020 is IDR 32,487.3 / Kg. While the results of forecasting the price of ordinary red chilies using the box-jenkins method with the SARIMA (1,0,0) (1,0,0) 12 model with the help of the MINITAB 19 program is the highest price of Rp. 32,967.8 / Kg which occurred in August. 2020 and the lowest price is IDR 16,756.4 / Kg which occurred in December 2020, while the average price of ordinary red chili in 2020 is IDR 23,346.27 / Kg.